Exploration of the Diversity of Trees and Its Implementation in the Plant Morphology Course - Nur Wijayanti; Maikel Simbiak; Edoward Krisson Raunsay (Postgraduate, University of Mataram, 2022)
The campus as an educational facility is always designed to create comfort that can support the quality of learning in it so the concept of green open space has long been part of the development of the campus environment. This study aims to determine tree species on the FKIP Universitas Cenderawasih (UNCEN) Abepura Campus and their implementation in learning plant morphology in the Biology Education Study Program. This research uses an exploratory method. The results of research on the Uncen Abepura FKIP Campus environment found 13 species with 10 families in the category of trees with a diameter of 20 cm and above. These trees are scattered in various environments on the FKIP UNCEN Abepura Campus. The Arecaceae family consists of two tree species, namely Cocos nucifera L and Livistona saribus (Lour.) Marr. The Cupressaceae family consists of one type of tree, namely Cryptomeria japonica. The Sapindaceae family consists of two types of trees, namely Filicium decipiens (Wight & Arn.) and Pometia pinnata. The Fabaceae family consists of two tree species, Albizia saman (Jacq.) Merr, and Tamarindus indica L. The Moraceae family consists of one tree species, namely Ficus benjamina. The Lecythidaceae family consists of one tree species, namely Barringtonia asiatica (L.) Kurz. The Combretaceae family consists of one type of tree, namely Terminalia catappa L. The Anacardiaceae family consists of one type of tree, namely Mangifera indica L. The Oxalidaceae family consists of one type of tree, namely Averrhoa carambola L. The Clusiaceae family consists of one type of tree, namely Calophyllum inophyllum L. Implementation of This research is in the form of learning media in the form of a plant morphology practicum guide